Higher Heart Weight in New Zealand Māori and Pacific Islanders. (September 2018) - Philcox, Winston; Garland, Jack; Zaidi, Faseeh; Morrow, Paul; Kesha, Kilak; Stables, Simon; Wong, Christopher X.; Spark, Amy; Tse, Rexson
Abstract : Abstract: Heart weight is dependent on sex, age, height, and weight. Although previous autopsy studies showed no differences in heart weight between different ethnic groups, none have examined the New Zealand population of Māori and Pacific Islanders (Polynesians). The presented study compared heart weights between 101 European and 85 Polynesian suicide hanging deaths from New Zealand. Univariate linear regression coefficients for age, male sex, height, body weight, body mass index, and Polynesian ethnicity were positive and significant ( P < 0.05). Apart from body mass index, subsequent multivariate analysis showed that all regression coefficients remained positive and significant ( P < 0.05). Polynesian ethnicity seemed to be an independent predictor for increased heart weight in the study population. Apart from possible genetic factors, the higher heart weight in Polynesians may have other underlying reasons. Caution is required when interpreting heart weight in cases of sudden natural deaths, especially in this population. Abstract : Supplemental digital content is available in the text.